Analyzing the adoption of hybrid electric and hydrogen vehicles in Indonesia: A multi-criteria and total cost of ownership approach - Hendri Bhirowo; Indrawati; Handrea Bernando Tambunan; Indra Ardhanayudha Aditya; Refi Rifaldi Windya Giri; Fasa Maulidan Hakim; Fayza Najeela Pakutandang (Cleaner Engineering and Technology)
Indonesia faces mounting challenges from climate change and environmental degradation, underscoring the need for sustainable transportation solutions. This study evaluates factors influencing the adoption of Hybrid Electric Vehicles (HEV), Battery Electric Vehicles (BEV), and Hydrogen Fuel Cell Vehicles (HFCV) using Multi-Criteria Analysis (MCA) and Total Cost of Ownership (TCO) approaches. Eight key factors were analyzed: safety, operational and maintenance costs, initial cost, government incentives, charging speed, resale value, and environmental impact. Findings reveal that safety concerns, particularly for hydrogen vehicles, rank as the highest priority for consumers, followed by cost efficiency and government support. Environmental considerations, while significant, were lower in priority. The study highlights the importance of targeted subsidies, enhanced safety features, and infrastructure investments to overcome barriers to adoption. By providing actionable recommendations, such as raising public awareness of the long-term benefits of environmentally friendly vehicles, this research supports policymakers in driving the transition to sustainable transportation in Indonesia. These insights contribute to addressing rising vehicle emissions and fostering the adoption of HEV5, BEV2, and HFCV6, aligning with Indonesia's broader climate goals.